Kualitas Peer Assessment sebagai Assessment Formatif - Adawiyah, Siti Rabiatul; Nofisulastri, Nofisulastri (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to produce a suitable peer assessment instrument as a formative assessment. This type of research is development research, because it develops a peer assessment instrument. The development of the peer assessment instrument refers to the Borg & Gall development model which includes 10 stages, namely: 1) a preliminary study; 2) planning; 3) development of a product initiation model; 4) reviewing the initiation model of the product; 5) revision; 6) limited trials; 7) revised trial results; 8) wide-scale trials; 9) final product revision; and 10) dissemination. However, in this study only up to stage 8, while stage 9 and stage 10 were not carried out due to time and conditions that did not allow. Expert validation was carried out beforehand before limited testing and wide-scale trials in Class X Madrasah Aliyah An-Najah, Al-Halimy Education Foundation, Sesela, Gunungsari District, West Lombok Regency. The results showed that the logical validity of the peer assessment instrument was very good, with an average score of 3.7. The results of the analysis using the product moment correlation test to determine the empirical validity of the peer assessment showed that the empirical validity of the peer assessment was in the high category (0.94; 0.96; 0.97; and 0.97). Based on the results of the study, it was concluded that peer assessment was of good quality as a formative assessment.